Calorific value and the potential of some plantation species for energy production. - Sahri, Mohd Hamimi; Nuruddin, Ahmad Ainuddin; Chee Ling, Lee (1991)
Four plantation species namely Acacia mangium, Gmelina arborea (Yemane), Paraserianthes falcataria (Batai) and Hevea brasiliensis (Rubber wood) and one palm species Elaeis guineesis (Oil palm) were selected for caloric content study. The calorific value of these species were determined using Laboratory Oxygen Bomb Calorimeter. The experiments were carried out at two different moisture content level : i.e at equilibrium moisture content (EMC) and oven dried conditions. The wood samples were first chipped, ground and made into pallet form then placed for room temperature conditioning to reach EMC. Two sets of wood samples required for the study, one with extractives and the other without extractives (extractives free). Results show that at oven dry condition, Gmelina arborea exhibited the highest calorific value of 4741 cal/g followed by Acacia mangium 4734 cal/g, Hevea brasiliensis 4676 cal/g, Paraserianthes falcataria 45363 cal/g and Elaeis guineesis 4271 cal/g. At EMC condition, the calorific value of these species were significantly lower than above values. The unextracted samples exhibited higher value compared to the extracted one. The calorific value of these wood species were greatly influenced by moisture content and extractive content and to the certain extent the density. Nevertheless, the density was important in influency the period of combustion. Although the calorific value of these wood were lower than other commonly used fuel, but since wood is a renewable resources and available in abundance, it is prudent to consider wood as a supplementary energy resources.